Gallery 9: The Blessed Anchorites of Puebla - Ojeda, Almerindo E. (PESSCA, 2014)
Maarten de Vos (1532-1603) was a prodigious Flemish draftsman whose alluring Mannerist designs were engraved by the hundreds in Northern Europe. Once engraved, these drawings traveled throughout the Spanish empire, serving as models for very many works of art. So many, in fact, that his impact on Spanish Colonial art is considered to be second only to that of Rubens. At the end of the 16th century Maarten de Vos produced more than a hundred drawings of anchorites--men and women who chose to withdraw from society in order to lead a life focused on prayer, penance, and religious study (see Gallery 8: The Blessed Anchorites of Cuzco). These drawings must have been immensely popular in their day, as they were quickly engraved in Antwerp and in Venice by three of the leading engravers of the time—Johan Sadeler I, Raphael Sadeler I, and Adriaen Collaert. These engravings were then engraved again, this time in reverse, and published in Paris by Thomas de Leu, Jean Leclerc IV, and Jacques Honervogt early in the 17th century. They were also published in Paris chez Daumont, rue Saint Martin. And in Venice by Giovanni Merlo, an engraver and publisher about whom little else is known. It was probably one of the Paris editions of the de Vos anchorites that served as the direct sources for eleven paintings currently at the Museum of the University of Puebla and one in the Francisco J. Ysita del Hoyo Collection. These twelve paintings—plus one we will talk about below—are what we have called The Series of the Blessed Anchorites of Puebla. Formerly attributed to Diego de Borgraf, the Flemish painter who emigrated to Puebla, the author of this 17th century series of paintings is now considered anonymous. Recently, the series of the Blessed Anchorites of Puebla was the object of an important study by Fernando E. Rodríguez-Miaja (see Rodríguez-Miaja 2001). This study succeeded in identifying the indirect sources of all the paintings of the anchorites in the series—namely the engravings by the Sadelers mentioned above. But the Sadeler engravings are reversed relative to the paintings. This suggests that the direct sources of the poblano paintings of the anchorites were not the engravings of the Sadelers, but only engravings based on them. And, of all the re-engravings mentioned above, there is but one that contains the images found in all of the paintings. It is the set published by Jean Leclerc IV [1]. It is therefore likely that it was this set that served as the direct source of our paintings. Jean Leclerc IV (ca. 1560-1633) was an engraver and publisher that worked at a workshop located in Paris, rue Saint Jean de Latran, under the sign of the Royal Salamander. It was there that he published the engravings of the anchorites in the first third of the 17th century. He published these engravings in a series of volumes which bore the same titles as the ones in which the Sadelers published their own renditions of the designs invented by Maarten de Vos. One of these volumes was the Trophaeum Vita Solitariae, whose title page we have reproduced above. Another was the Solitudo Sive Vitae Partrum Eremicolarum. A third was the Monumenta Anachoretarum (sometimes referred to as Sylvae Sacrae). The title pages of the latter two volumes are shown below. In addition to proposing direct sources for all of the poblano paintings of the anchorites, the correspondences found in this gallery will correctly identify the subject matter of one of the paintings of the series (Saints Euthymius and Theoctistus), locate the whereabouts of a second (Saint Helenus), and identify the engraved source of a third (Saint Onuphrius) [2]. In addition, they will place the thirteenth painting of this series—a Temptation of Christ—in correspondence with one of the engravings of the Evangelicae Historiae Imagines (see Gallery 1). It should perhaps be added that a painting of the temptations of Christ fits within a series of anchorites because, as Rodríguez-Miaja pointed out, this temptation took place when Christ withdrew to the desert as an anchorite in order to pray for forty days and forty nights. Following the navigation panel below will lead the visitor through the correspondences of this gallery. 1. At least according to the copies catalogued in Bartsch 1978-Present 70(2)(Supplement) and (71)(1)(Supplement). The reversed copy of Saint Helenus in the Newberry Library of Chicago was published by Jean Leclerc IV (See item ZX 639 .L462 at the Newberry Library). 2. The painting of Saint Onuphrius was not among the ones Mr. Rodríguez-Miaja was able to study. Fortunately, this painting is now in view at the Museum of the University of Puebla. It was there that we were able to study it in 2010. PESSCA is indebted to Denise Beck Garreaud and Marcela Corvera Poiré for the support they provided to the research that led to the installation of this gallery.
Keywords: Anacoretas de Vos; Arte europeo; http://purl.org/pe-repo/ocde/ford#6.03.00